Fat pattern of athlete and non-athlete girls during puberty - Pápai, Julia; Tróznai, Zsófia; Szabó, Tamás; Szabó, Attila (Anthropological Review, 2012)
The study focused on the peculiarities of fat accumulation during maturation. The main purpose of the study was trifold: to detect the alterations in fat gain during breast maturation; to examine fat accumulation after physiological maturation and the influence of breast maturation and sport activity on fatness. The subjects were athlete (N=1428) and non-athlete (N=1030) girls. They were grouped by the stages of breast development. Fat accumulation was followed up until four years after menarche. Regional fat distribution was examined on the basis of skinfolds taken at triceps, scapula, abdomen and thigh. Progressing with breast development, body fat percent increased in both groups, though in non-athletes a decrease was found in stage B4. During sexual maturation the thickness of subcutaneous adipose tissue decreased on the extremities and increased on the trunk. Non-athletes stored more fat on their upper trunk, while athletes did it on their lower trunk. After menarche the differences between athlete and non-athlete girls were preserved. In conclusion it may be stated that during sexual maturation the regional apposition trend of body fat was similar for athletes and non-athletes. The differences emerged in the relative distributions. Athlete girls accumulated proportionally more fat on their lower body, representing better the female-type distribution of body fat than non-athlete girls.